A strategic maintenance management model: enhancing defect resolution efficiency in local government infrastructure - Abdullah, Ahmad Sharim; Mohammed Ali, Irwan; Mohd Radzuan, Nor Amin (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
This product introduces an innovative Strategic Maintenance Management (SMM) model aimed at improving the efficiency of defect resolution in local government infrastructure. Recognizing the growing public demand for quality services and the growing role of local government, this model emphasizes the importance of integrating strategic management principles into the maintenance process. Although previous studies in Malaysia have highlighted the importance of strategic planning in maintenance management, they have often lacked focus on innovative, entrepreneurial-driven approaches tailored to the local context. The proposed SMM model addresses this gap by incorporating a proactive strategy that streamlines maintenance workflows, optimizes resource allocation, and fosters collaborative innovation among stakeholders. By emphasizing agility and entrepreneurship, this model is expected to transform maintenance management from a reactive, cost-driven function to a value-generating asset for local governments. Preliminary findings suggest that implementing such a framework not only improves operational efficiency but also promotes sustainable development and public trust in municipal services. This research contributes to the discourse on strategic innovation in public sector management and provides actionable insights for local governments seeking to align their maintenance practices with contemporary demands for service excellence and entrepreneurial thinking.